Review of System Dynamics models for electricity market simulations - Felix Teufel; Michael Miller; Massimo Genoese; Wolf Fichtner (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2013)
This paper provides a review on modeling electricity markets with System Dynamics (SD) focusing on deregulated electricity market models. First the SD method is classified within the wide field of electricity market modeling. Then all distinctive properties of the SD method in this context are elaborated. After an overview of first SD models in energy economics, a comprehensive review of models of deregulated electricity markets is presented. The review captures more than 80 publications in the field of SD energy market modeling. Some tendencies could be identified: Firstly SD models are more and more combined with other methods like generic algorithms, experimental economics or analytical hierarchy processes. Secondly, stochastic variables are considered increasingly. Thirdly, models show a higher level of detail and increasingly evaluate aspects such as new markets designs or new market components and their interdependencies.
urn:nbn:de:swb:90-347325
Keywords: 330; Deregulated electricity market; market model; market design; system dynamics; model review; investment decisions; regulation; market power; evaluation of strategic concepts